Multi-method approach shows stock structure in Loligo forbesii squid. (21st March 2022) - Sheerin, Edel; Barnwall, Leigh; Abad, Esther; Larivain, Angela; Oesterwind, Daniel; Petroni, Michael; Perales-Raya, Catalina; Robin, Jean-Paul; Sobrino, Ignacio; Valeiras, Julio; O'Meara, Denise; Pierce, Graham J; et al.
Abstract: Knowledge of stock structure is a priority for effective assessment of commercially-fished cephalopods. Loligo forbesii squid are thought to migrate inshore for breeding and offshore for feeding and long-range movements are implied from past studies showing genetic homogeneity in the entire neritic population. Only offshore populations (Faroe and Rockall Bank) were considered distinct. The present study applied mitchondrial and microsatellite markers (nine loci) to samples from Rockall Bank, north Scotland, North Sea, various shelf locations in Ireland, English Channel, northern Bay of Biscay, north Spain, and Bay of Cadiz. No statistically significant genetic sub-structure was found, although some non-significant trends involving Rockall were seen using microsatellite markers. Differences in L. forbesii statolith shape were apparent at a subset of locations, with most locations showing pairwise differences and statoliths from north Ireland being highly distinct. This suggests that (i) statolith shape is highly sensitive to local conditions and (ii) L. forbesii forms distinguishable groups (based on shape statistics), maintaining these groups over sufficiently long periods for local conditions to affect the shape of the statolith. Overall evidence suggests that L. forbesii forms separable (ecological) groups over short timescales with a semi-isolated breeding group at Rockall whose distinctiveness varies over time.